Simple methods for identification of plastics - Braun, Dietrich (Hanser Publishers, 2013)
Processors and users of plastics often need to determine the chemical nature of a plastics specimen. The highly practial and useful manual will enable you to determine the class of plastics of the specimen. No extensive knowledge of chemistry is required and yet it is far more than a simple tabular compilation. It is a handy and highly effective tool for many practical situations.
Keywords: Plastics -- Analysis.; elektronické knihy; electronic books